IMPLEMENTATION OF SOLAR ENERGY FOR PUBLIC STREET LIGHTING IN SEGOROGUNUNG VILLAGE, KARANGANYAR REGENCY - Ghoni, Ruzlaini; Joharwan, Johanes Wawan; Jamaldi, Agus; Purwono, Arif Hidayat; Rifai, Damhuji; Nugroho, Wasis; Susanto, Husein Arif; Ramadhan, Ichsan (Abdi Masya, 2024)
The world's energy sources have undergone several changes, from initially mostly using biomass to fossil fuels, which was triggered by the Industrial Revolution in the 1900s. The increasing use of fossil energy causes an increase in greenhouse gas emissions. One alternative that can be done is the use of solar power plants. An example of its use is in fulfilling electrical energy, such as lighting, by using electrical energy that still uses a small amount of power. Sekolah Tinggi Teknologi “Warga” Surakarta of Indonesia, together with UC TATI Malaysia, collaborated in the use of solar-based renewable energy, which was implemented in Segorogunung Village, Ngargoyoso District, Karanganyar Regency. Several points at this location still have minimal lighting, making them prone to accidents and crime. The method used in this community service activity is providing knowledge about solar cells, solar cell wiring diagrams, and how to check and repair solar-based public street lighting. The results obtained from this community service show that the community understands and can install and repair solar cell-based public street lighting. In conclusion, the presence of public road lighting on several roads in Segorogunung Village can reduce the accident rate and provide a sense of security for the community when crossing the road.